Antibacterial activities of the phytochemicals-characterized extracts of Callistemon viminalis, Eucalyptus camaldulensis and Conyza dioscoridis against the growth of some phytopathogenic bacteria. (December 2017) - EL-Hefny, Mervat; Ashmawy, Nader A.; Salem, Mohamed Z.M.; Salem, Abdelfattah Z.M.
Abstract: Three bacterial isolates were isolated from infected potato tubers showing soft and brown rots like symptoms as well as one isolate from infected peach tree showing crown gall symptom. The morphological, biochemical and molecular assays proved that bacterial isolates belonging to Pectobacterium carotovorum subsp. carotovorum, Ralstonia solanacearum, Dickeya spp. and Agrobacterium tumefaciens . The acetone (AcE) and n -butanol (ButE) extracts of Callistemon viminalis flowers and essential oil from aerial parts of Conyza dioscoridis as well as ButE of Eucalyptus camaldulensis bark are evaluated at different concentrations against the growth of the isolated bacteria. The diameter of inhibition zone (IZ) and the minimum inhibitory concentrations (MICs) are compared. Results indicated that the highest IZ values were 20.0 mm and 18.3 mm for E. camaldulensis bark ButE and C. viminalis flower ButE, respectively, against P. carotovorum ; 16.3 mm and 16.0 mm for E. camaldulensis bark ButE and C. viminalis flower ButE, respectively, against R. solanacearum ; 18.5 mm for C. viminalis flower AcE and C. dioscoridis aerial parts EO against Dickeya spp.; and 15.0 mm for C. viminalis flower AcE against A. tumefaciens . MICs ranged from <16 μg/mL for D. solani to >4000 μg/mL for A. tumefaciens . It was proved that C. viminalis flowers AcE contains mainly 5-hydroxymethylfurfural (20.6%), palmitic acid (18.5%), and pyrogallol (16.4%); while C. viminalis flower ButE contains palmitic acid (36.3%), 2-hydroxymyristic acid (9.4%), 5-hydroxymethylfurfural (7.2%), and shikimic acid (6.6%); whereas E. camaldulensis bark ButE contains 8-nonynoic acid methyl ester (45.6), camphor (30.9%), menthol (8.8%), and 1, 8-cineole (eucalyptol) (8.2%), whilst the EO of C. dioscoridis aerial parts comprises Z -(13, 14-epoxy)tetradec-11-en-1-ol acetate (11.6%), γ -elemene (10.2%), tau.-muurolol (7.1%), and cadina-3, 9-diene (4.7%). It can be concluded that phytochemical extracts of C. viminalis, E. camaldulensis and C. dioscoridis demonstrated strong to moderate antibacterial effects against the studied plant bacterial pathogens. Graphical abstract: Highlights: Some phytopathogenic bacteria were isolated from infected Potato and Peach plants. Natural products of some woody plants were assayed against the isolated bacteria. E. camaldulensis bark extract showed MIC of 16 μg/mL against P. carotovorum . MIC values of C. viminalis flower extract with R. solanacearum and A. tumefaciens . Strong activity against Dickeya spp. by C. viminalis and C. dioscoridis extracts.